When banks hold back: Credit and liquidity provision - Carlo Altavilla; Massimo Rostagno; Julian Schumacher (European Central Bank (ECB), 2025)
Banks are reluctant to tap central bank backup liquidity facilities and use the borrowed funds for loans to the real economy. We show that excessively parsimonious borrowing and lending can arise in a stigma-free model where the banking sector has an incentive to overissue deposits. Banks don't heed the central bank's call for more credit to finance investment because they simply ignore the collective gains from stronger activity in their atomistic decisions. Central banks can address this market failure by disintermediating market-based finance. A lender-of-last-resort (LOLR) system in which the central bank offers liquidity liberally but on non-concessionary conditions improves over a pure laissez-faire arrangement, where asset liquidation in the marketplace is the only source of emergency liquidity. But under LOLR banks remain reluctant to intermediate. Credit easing (CE) and quantitative easing (QE), instead, can stimulate bank borrowing and repair the broken nexus between liquidity provision and credit. Empirical analysis using bank-level and loan-by-loan data supports our model predictions. We find no empirical connection between loans and borrowed reserves obtained from conventional refinancing facilities. In contrast, there is a robust connection between loans and structural sources of liquidity: reserves borrowed under a CE program or non-borrowed, i.e. acquired from a QE injection. We also find that firms with greater exposure to banks borrowing in a CE program or holding larger volumes of non-borrowed reserves increase employment, sales, and investment.
Keywords: E5; E43; G2; 330; Lending of last resort; credit easing; quantitative easing; loans; reserves